Peningkatan Mutu Guru dalam Proses Pembelajaran melalui Penerapan Supervisi Klinis Pengawas Sekolah di SD Gugus 1 Kecamatan Sekongkang Tahun 2020 - Wahidin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
The purpose of this supervisory action research (PTKp) is to determine the extent to which principal coaching through clinical supervision is to improve teacher performance in implementing learning. In this PTKp is carried out in 3 cycles, from the results of the actions taken are proven to improve teacher performance by achieving ideal standards. From 63.40% in the first cycle, it can increase to 73.00% in the second cycle, and 83.00% in the third cycle. The results of this action research indicate that coaching through clinical supervision can improve teacher performance in implementing learning, with completeness reaching 100%.